PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI KELAS XI IPS 1 SMA NEGERI 12 MAKASSAR. - Nur, Baiatun Nisaa (UNIVERSITAS NEGERI MAKASSAR, 2018)
The results showed an increase in the geography learning outcomes of XI IPS 1 students at Makassar State High School 12 after the problem based learning model was applied with the following indications: 1) the learning value of the geography of students in which 71.34% experienced a learning model of learning problems improvement after applied problem based learning models in the first cycle of 73.81% including the medium category and the second cycle 79.01% including the high category, with an increase in the percentage of 6.58%, 2) the results of observations of student activities in teaching and learning activities experienced changes, at cycle I 46.7% experienced changes in student learning activities in the second cycle 59.4% with the active category. This means experiencing improved attitude from the previous cycle. It is recommended: 1) geography teachers should be creative in creating a classroom atmosphere so that students are not bored and comfortable in presenting material while learning and are more motivated in paying attention to what is taught, 2) it is best for the school to maximize facilities and infrastructure in schools, provide textbooks in library.